PERAN POLA ASUH DAN MEDIA YOUTUBE TERHADAP PEMEROLEHAN BAHASA PADA ANAK USIA 3 TAHUN - Rina Zulvia; Lu’lu Naura Nur Syahidah; Dona Aji Karunia Putra (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the role of parenting styles and YouTube media on language acquisition in three-year-old children. This study uses a descriptive qualitative method. The subjects in this study were two three-year-old children, consisting of one boy and one girl with different parenting styles. The data in this study consisted of the utterances and responses produced by both children during their daily interactions and when accessing YouTube media. The data collection techniques applied in this study included participatory and non-participatory observation, recording, and language comprehension tests. The results of the study show that children's language acquisition is characterized by sound substitution, phoneme deletion, and simplification of word structure. However, their language comprehension skills developed well. Responsive parenting plays an important role in supporting language development, while YouTube becomes an additional source of linguistic input with parental guidance.